Can Institutional Transplants Work? A Reassessment of the Evidence from Nineteenth-Century Prussia - Jeremy Edwards (Center for Economic Studies and ifo Institute (CESifo), 2021)
The institutional reforms France imposed in the parts of Germany it occupied in the late eighteenth and early nineteenth centuries are claimed to provide an example of successful externally-imposed institutional reforms. The most detailed study is that of Lecce and Ogliari (2019), who argue that the effectiveness of transplanted French institutions in different parts of Prussia depended on the cultural proximity between France and the relevant part of Prussia. However, Lecce and Ogliari take no account of a widely-recognized feature of nineteenth-century Prussian economic development: the importance of regional effects. The French reforms were concentrated in the west of Prussia, which was more economically advanced than the east before the French invasion, and this pre-existing difference must be disentangled from the effect of the French reforms in order to identify the effect of the latter. Once this is done, the evidence shows neither any favourable effect of French rule nor an effect of cultural proximity on the impact of French rule.
Keywords: N13; O43; O52; 330; institutional reform; regional effects; omitted variable bias